Opinión de la población graduada, con respecto a sus necesidades de formación y actualización profesional de la carrera de Bibliotecología y Documentación, de la Universidad Nacional de Costa Rica - Ocampo Bermúdez, Giannina (2020)
The purpose of this study is to identify and ask the opinion of the population that has obtained a degree in Library and Information Science from Costa Rica’s National University, regarding their studies and updating needs and training, in order to strengthening their academic and labor skills. This research had a quantitative and descriptive approach. Data collection was made through a digital questionnaire that was applied to 60 persons graduated between 2010 and 2018. With the results, a profile of the graduated person could be obtained. The findings also showed information about the appropriateness and availability of means and resources during career learning,information about current work locations,about professional performance,about professional growth and improvement andsome comments and suggestions for improvement.